Survey on test collections and techniques for personal name matching. (4th October 2006) - Reuther, Patrick; Walter, Bernd
This paper gives an overview of personal name matching. Personal name matching is of great importance for all applications that deal with personal names. The problem with personal names is that they are not unique and sometimes even for one name many variations exist. This leads to the fact that databases on the one hand may have several entries for one and the same person and on the other hand have one entry for many different persons. For the evaluation of personal name matching algorithms, test collections are of great importance. This paper gives an overview of existing test collections and presents two new test collections based on real-world bibliographic data. Additionally, state-of-the art techniques and a new approach based on semantics are also described.